Oral Rule in Criminal Court proceedings - Atshan Khawaf Shallal Al-Zaidi, Alaa; Hammad Hamid Hamad, Prof.Dr. Hassan (Basra studies journal, 2022)
Most of the penal legislations have adopted the rule of oral as a guarantee of the rights of the accused in a fair trial, through which the accused can defend himself and return any evidence used against him and infringing his innocence, because this rule guarantees the right of the parties to the dispute, as it is a guarantee that the trial procedures are oral, and through it The litigants can be confronted, discussed and questioned about all the evidence presented to the court, and through this the judge’s conviction is formed as a result of the oral discussion of the evidence presented before him. Including what is related to the documents submitted to the court to prove or deny the accusation, and these exceptions do not mean neglecting this rule or violating the rights of the litigants, but rather they reduce the application of the rule imposed by some legal texts and circumstances, so the court is forced as a result not to apply it.